Operational Risks Faced by Financial Institutions in the Digital Age: A Case of Nigeria - Ikenna, Michael (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine operational risks faced by financial institutions in the digital age: a case of Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that financial institutions in Nigeria are confronted with a myriad of operational risks in the digital age, stemming from the rapid adoption of technology and the evolving cyber threat landscape. The shift towards digital banking and fintech innovations has introduced new vulnerabilities, including cyberattacks, data breaches, and fraudulent activities, posing significant challenges to the security and integrity of financial systems in Nigeria. Operational risks associated with technological disruptions, such as system failures, IT outages, and disruptions to digital payment platforms, can undermine the reliability and efficiency of financial services, leading to customer dissatisfaction and financial losses. The proliferation of mobile banking and digital payment channels has heightened concerns about financial inclusion, data privacy, and regulatory compliance, necessitating robust risk management frameworks and regulatory oversight to safeguard the stability and resilience of Nigeria's financial sector. Unique Contribution to Theory, Practice and Policy: Technology Acceptance Model (TAM), Agency Theory & Resource Dependence Theory may be used to anchor future studies on operational risks faced by financial institutions in the digital age: a case of Nigeria. Financial institutions should prioritize the implementation of robust cybersecurity measures, including regular security audits, penetration testing, and employee training programs. By enhancing cybersecurity awareness and preparedness, institutions can mitigate the risk of cyberattacks and data breaches. Regulatory authorities play a crucial role in shaping the regulatory landscape to address operational risks in the Digital Age. Policymakers should collaborate with industry stakeholders to develop robust regulatory frameworks that promote innovation while safeguarding financial stability and consumer protection.